2011
DOI: 10.1007/s10120-011-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

A multiple-center phase II study of weekly docetaxel and oxaliplatin as first-line treatment in patients with advanced gastric cancer

Abstract: Background Docetaxel and oxaliplatin are active agents for advanced gastric cancer (GC). The combination of these two drugs in a triweekly schedule is an active and attractive regimen for gastric cancer but with significant hematological toxicities. A multicenter phase II study was designed to establish an active regimen with good tolerability by using a weekly docetaxel-oxaliplatin (DO) combination in GC patients.Methods Eligible patients had histologically confirmed stage IV gastric cancer without previous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There is no standard chemotherapy regimen for advanced gastric cancer. Studies [ 21 24 ] have revealed that different chemotherapy regimens have similar efficacies for advanced gastric cancer, but these efficacies were all unsatisfactory. Present literatures have revealed that combined chemoradiotherapy could improve efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard chemotherapy regimen for advanced gastric cancer. Studies [ 21 24 ] have revealed that different chemotherapy regimens have similar efficacies for advanced gastric cancer, but these efficacies were all unsatisfactory. Present literatures have revealed that combined chemoradiotherapy could improve efficacy.…”
Section: Discussionmentioning
confidence: 99%